ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENANAMAN MODAL DALAM NEGERI (PMDN) DI JAWA TENGAH PERIODE 1985-2010 - Azar Fuadi (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2014)
Investment or capital investment is an important factor for increasing economic growth of a region. The purpose of this research is to find out and analyze whether the credit interest rate, PDRB, and the inflation levels influence toward Domestic investment in Central Java in the year of 1985-2010 partially or simultaneously. The variables which are being measured are the credit interest rate, gross domestic regional product, inflation level as free variable, national capital investment as tied up variable. The models which have been used are bifilar regression analysis with double log model, with regression comparison form Ordinary Least Squares (OLS).The research results show that the credit interest rate have some disadvantages and significant toward Domestic investment with the amount of distribution of -0.173288%, GDRP does not affect toward Domestic investment, the beneficial inflation levels and significant toward Domestic investment with the amount of 0.019231%. The F-statistic value amount of 3.194271 and the significance rate amount of 0.043467 with the inflation levels influence significantly toward Domestic investment in Central Java, whereas the determination coefficient (R2) that is 0.703419, it means that Domestic investment variables amount of 70,34% determined by the credit interest rate variations, GDRP, and the inflation levels, the remainder amount of 29,66% determined by another factor outside the models.The advice for this research is Bank Indonesia as central bank have to commit the credit interest rate and inflation control policy so it can increase Domestic investment in Central Java.